Od sukcesu tygodnika do niszowego miesięcznika. Zarys historii „Uważam Rze” - Kalbarczyk, Maciej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article gives an account of the turbulent history of the Polish news magazine Uważam Rze and provides a diagnosis of the successes and the failures of the weekly. Starting with an overview of the situation in the market of weekly opinion magazines in Poland and an account of the circumstances surrounding the founding of the magazine by a group of so-called “rebellious” journalists, the article then explores changes in the Presspublica company and the influence they had on the format and profitability of Uważam Rze. The research is based on archive issues of Uważam Rze and on information related to events surrounding the magazine. Statements by the founders of the weekly and their views, the opinions of media experts, and an analysis of circulation numbers show why Uważam Rze became so successful and how its potential was lost. The results of this analysis show that the reader–columnist relation represents far more than the mere habit of reading a particular magazine – in place of Uważam Rze, two new weeklies emerged (Do Rzeczy and wSieci) and they immediately took over part of the magazine’s readership. On the other hand, the complicated relations between the publisher and the editor-in-chief illustrate how important the financial independence of a magazine may be when it comes to a press free from any outside pressures.